Risk and QoE Driven Channel Allocation in CRN. (2016) - Mashoodha, P.V.; Kumar, K.S. Vipin
Abstract: Today, wireless multimedia applications are growing fastly and they require high bandwidth. Due to the limited spectrum resources, we cannot provide separate spectrum bands for each individual wireless multimedia application. Cognitive radio plays a vital role in providing spectrum resources to these applications. Cognitive radio enables wireless users to sense temporal and spatial unused channels and correspondingly adapt their transmission strategies. These unused channels may be occupied by the primary users(PUs) at any time, creating those channels unstable, which makes it difficult to meet the QoE requirement of secondary users using these unstable channels. Therefore it is essential to study how to manage the available spectrum resources among a set of secondary users based on their QoE requirement and stability of these channels. Historical QoE under different channels are investigated by SUs and these data are sent to cognitive radio base station(CRBS) and this base station allocates the channel based on QoE requirement and the historical data. At the time of any change in channel allocation due to arrival or departure of any user in the system, channel allocation should be modified such that degradation of QoE due to channel switching should be minimal.